Inside Back Cover: "Molecular Activity Painting": Switch‐like, Light‐Controlled Perturbations inside Living Cells (Angew. Chem. Int. Ed. 21/2017). Issue 21 (12th April 2017) - Chen, Xi; Venkatachalapathy, Muthukumaran; Kamps, Dominic; Weigel, Simone; Kumar, Ravi; Orlich, Michael; Garrecht, Ruben; Hirtz, Michael; Niemeyer, Christof M.; Wu, Yao‐Wen; Dehmelt, Leif
Abstract : People all around the world carve their initials into trees as a symbol of eternal love. But those carvings are about 1 million times larger than the paintings that were made in living cells by Y.‐W. Wu, L. Dehmelt, and co‐workers in their Communication onpage 5916 ff. Although these cell paintings were not made for eternity, they lasted for several hours––a very long time in the dynamic environment of a living cell. The paintings were made not just for fun, but were used to manipulate cell function to reach a better understanding of complex disease processes such as cancer metastasis.